Mapeamento de processos: um diagnóstico para melhoria no processo de embalagem de palmito em uma fábrica na cidade de Abaetetuba - MARTINS, Francenilda Matias (2024)
This work aims to show the applicability and the combination of two process mapping techniques widely used: the flowchart and the process map in Palmetto packing process, tracing a diagnosis of the process and doing a redesign of the same with the proposed improvement in this regard one must have a thorough understanding of the activities that compose the production process. Therefore, we used some process mapping techniques. Thus it sought to provide a more complete and transparent view of the process. The methodology applied through a descriptive case study, exploratory, quantitatively and qualitatively in a Palmetto plant located in the town of Abaetetuba-PA. Data collection method used is observation and measurement were plotted on spreadsheets in Excel, for further analysis and definition of the proposed improvements. The survey was conducted in two phases. The first phase consisted of a literature search with the process definition, process mapping, process management description Palmetto packing process. In the second phase of the tools applications were made: flowchart and process map, both enabled them to have a better view of the process and its activities. The result presents a proposal for improvement of the palm bottles packaging process showing a more streamlined process, with lower cycle times and adding more value to the final process.